Implementasi Maqasid Syari’Ah Dalam Perencanaan Keuangan Syariah Untuk Meningkatkan Kesejahteraan Finansial Berkelanjutan - Syam, Surya Darma; Maskanah, Siti; Anam, Khaerul; Sahroni, Sahroni (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2026)
Abstract This study analyzes the implementation of maqasid al-shariah within the domain of Islamic financial planning and its contribution to enhancing sustainable financial well-being. Maqasid al-shariah, as the overarching objectives underlying the establishment of Islamic law, encompass five fundamental dimensions: the preservation of religion (hifzh al-din), life (hifzh al-nafs), intellect (hifzh al-‘aql), lineage (hifzh al-nasl), and wealth (hifzh al-mal). In the financial context, the aspect of hifzh al-mal constitutes the principal foundation that must be safeguarded through financial planning grounded in sharia principles, including the avoidance of riba (usury), gharar (uncertainty), and maisir (gambling), as well as the application of Islamic social finance instruments such as zakat, infaq, sadaqah, and waqf. A descriptive qualitative method employing a literature review approach is utilized to map the understanding and practical implementation of these maqasid. The findings indicate that financial planning integrated with maqasid al-shariah encourages Muslims to manage their finances responsibly, adopt a long-term orientation, and consider social as well as spiritual dimensions. This integration generates positive impacts on both individual and societal welfare in accordance with the principles of justice and sustainability. Therefore, the implementation of maqasid al-shariah in financial planning plays a strategic role in fostering sustainable financial well-being that brings prosperity in both worldly life and the hereafter.